Peningkatan Hasil Belajar IPAS Melalui Website Google Sites pada Kelas IV Sekolah Dasar - Kristina Maisaroh; Endang Sri Maruti; Suprihatin Suprihatin (Universitas Maritim AMNI Semarang, 2024)
This research aims to improve the learning outcomes of class IV students at SDN Munggut 01 in the science subject. This research is classroom action research. This research was carried out at SDN Munggut 01 with research subjects in class IV as many as 15 students. The data collection techniques used in this research are observation, tests and documentation. Based on classroom action research (PTK) using Google Sites learning media to improve student learning outcomes in science and science subjects, the material on changing the shape of objects in the classroom has been implemented with the results of improvements through the data that has been obtained. The increase can be seen in learning outcomes with the average score of students in class IV with a presentation of completeness of learning outcomes in cycle I of 26.67%, while in the learning process of cycle II the percentage of completeness of student learning outcomes was 86.67%. The data shows that there was a significant increase in student learning outcomes in the science content material on changes in the form of objects through the learning media Google Sites.